The Effectiveness of Earthquake Disaster Mitigation Education on Improving the Knowledge of Students at SMP Negeri 1 Pancur Batu Deli Serdang - Meutia Nanda; Ririn Hasrat Kartika Zalukhu; Tia Wahyuni Dolok Saribu; Zahra Dwi Andini; Nabilla Suci Ramadhani; Restu Rahayani Padang (Universitas Ibn Khaldun Bogor, 2026)
Indonesia is a country with a high level of vulnerability to earthquakes because it is located in the Ring of Fire. The low level of students' knowledge about earthquake mitigation measures shows the need for early disaster education. This study aims to determine the effectiveness of earthquake mitigation education in increasing the knowledge of students at SMP Negeri 1 Pancur Batu. This study used a quantitative method with a one-group pretest-posttest design with a sample of 57 ninth-grade students. The intervention was carried out through counseling using PowerPoint, educational videos, question and answer sessions, and earthquake simulations. The results showed an increase in the average knowledge score from 43.05 on the pretest to 55.30 on the posttest. The paired sample t-test statistical test showed a p-value = 0.001 (p < 0.05), indicating a significant difference between the pretest and posttest scores. These findings show that earthquake mitigation education is effective in increasing students' knowledge. Similar education and simulation programs are recommended to be carried out regularly to strengthen disaster preparedness in the school environment.